Predicting sukuk default probability and its relationship with the sukuk rating level: case study of sukuk in Malaysia - Ardiansyah, Misnen; Haron, Razali; Qoyum, Abdul (2012)
The aim of this study is to reexamines to what extent capital management and income smoothing through PER. The results are important in assessing financial stability along with the depositors’ confidence. Overall, we find evidence that capital management is an important determinant of PER. By using a panel of fifteen IBIs, our study indicates that CAR is significant and contrary to current practices of PER. The higher capital ratio, the banks can generate more income from the capital. The higher income can give a higher hibah based on the deposit and smooth the profits attributed to depositors. Second, we find that the Islamic banks follow the income smoothing behavior. This results found that, the reserve (PER and IRR) use by Islamic banks can stable the result and profit payout attributed to the depositors based on hibah. The objective of PER is to stabilizing the rate of return to depositors and to ensure that the rates of return of deposit of the IBIs to remain competitive and stable. Based on our finding, Islamic banks use the PER and IRR to stable the results. The Shariah issue highlighted by Shahruddin (2011) that the practice of having a certain amount of profit as reserve for time of bad business is totally unknown to the classical mudharabah contract. Further research is therefore needed to study the shariah issue regarding the implementation of PER. We support the recommendation by Taktak et al. (2010) that the regulators need to enhance the disclosure on the specific reserve used by Islamic financial institutions to avoid financial system distress. Even though there are empirical evidence on PER and IRR provisioning behavior for Islamic banking institutions, evidence on other type of financial institutions are rather scarce. Based on our study, For instance, for Malaysian case, there are other institutions offering Islamic financial product and services, i.e. developmental financial institutions like Agro Bank, SME Bank, Bank Simpanan Nasional (BSN), as well as cooperative bank like Bank Rakyat. It will be more interesting to investigate these non-commercial banking institutions. Some interesting questions to ask are do they have other mechanism serving as reserves, such as share or insurance to absorb risk or to stabilize return?